Analisis Pengaruh Rasio Profitabilitas dan Solvabilitas Terhadap Harga Saham Perusahaan Sektor Pertambangan - Tio Waskito Erdi (Journal of Trends Economics and Accounting Research, 2025)
The research conducted aims to determine and analyze the profitability ratio and solvency ratio in determining the stock price of mining sector companies after the global Corona Virus (Covid-19) pandemic. Research Method: The research conducted is a type of quantitative research, the population used in this study are mining sector companies listed on the IDX for the 2021-2023 period which is the period after the Covid-19 pandemic. The companies used as samples in the study were 14 companies with purposive sampling techniques, in this study using multiple linear regression analysis with the SPSS test tool. The results of the study showed that Return on Asset (ROA) had no effect on stock prices, Return on Equity (ROE) had no effect on stock prices, Debt to Equity Ratio (DER) had no effect on stock prices, and only Earning Per Share (EPS) had an effect on stock prices. From the results of the study, it was concluded that in the post-pandemic context, EPS showed a significant influence on the stock prices of companies in the Indonesian mining sector.